(untitled) (Eurasian Research Bulletin, 2023)
It is not a secret that the artistic text as an artistic-aesthetic whole is a complex and multi-layered phenomenon. Understanding the main idea - thought - content expressed in an artistic text is not just a task, but a very difficult and complex creative process. In order to understand the content of any text, it is necessary and sufficient to know the lexicon and grammar of the language, in order to understand the content of the artistic text, it is also necessary to know the specific linguistic and poetic laws of the artistic text. Linguistics is the main factor in achieving the skill of correct philological interpretation, analysis and perception of literary text, deep aesthetic pleasure and information acquisition. This article analyzes some linguopoetic features of Muhammad Yusuf’s poetry